TINJAUAN TENTANG PERJANJIAN JUAL BELI RUMAH DENGAN AKAD MUSYARAQAH MUTANAQISHAH MENURUT UNDANG–UNDANG NO 21 TAHUN 2008 TENTANG PERBANKAN SYARIAH (Studi Pada Bank BTN Syariah Cabang Pekanbaru) - Luthfi Rabbani; Firdaus Firdaus; Meriza Elfa Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Bank BTN Syariah Pekanbaru Branch as a PT engaged in banking offersSharia mortgage services with the help of subsidies from the government to begiven to people with certain incomes. In its implementation, Bank BTN SyariahPekanbaru Branch first buys the house that the customer wants and then sells itback to the customer using the Musyaraqah Mutanaqishah contract. The purposeof writing this thesis: First, to find out how the implementation of Islamicmortgage financing carried out by PT. Bank BTN Syariah Pekanbaru Branch.Second, what efforts must be made so that the agreement between Bank BTNSyariah Pekanbaru Branch and customers is in accordance with shariaprinciples?The type of research used in this legal research is sociological legalresearch. Where, the research location coincides in the city of Pekanbaru.Analysis of the data used is the author analyzes the data qualitatively. In drawingconclusions the author uses the method of deductive thinking.The results of the study show that the Sharia KPR agreements entered intobetween Bank BTN Syariah Pekanbaru Branch and the customer use theMusyaraqah Mutanaqishah Agreement, but in terms of implementation thiscontract is not appropriate for use in providing Sharia KPR services tocustomers. This is because the bank has first purchased the object to be tradedand then resold it to the customer, with a scheme like this the contract that shouldbe used is aka murabahah. Efforts must be made so that agreements betweenBank BTN Syariah Pekanbaru Branch and customers are in accordance withsyriac principles, namely by ensuring that the contracts used are in line withIslamic law and maximizing the role of DPS in supervising and guaranteeing theimplementation of Sharia Banking operations in accordance with the principlesand values in law Islam.Keywords: Sale and Purchase Agreement – Akad – Sharia Principle